If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+5(-4-13)=-169
We simplify the equation to the form, which is simple to understand
7x+5(-4-13)=-169
Simplifying terms in parentheses
7x+5*(-17)=-169
Reorder the terms in parentheses
7x+(-85)=-169
Remove unnecessary parentheses
+7x-85=-169
We move all terms containing x to the left and all other terms to the right.
+7x=-169+85
We simplify left and right side of the equation.
+7x=-84
We divide both sides of the equation by 7 to get x.
x=-12
| 4x+50=8x-10 | | -9=-4+x/13 | | 83-3x=15x+21 | | 4w+2=18 | | 14-8x=89-29x | | -6x+6(-2x-12)=144 | | 2a^2+18a+28= | | 9x(2x+7)= | | 2345x-678=678 | | 5(3-2x)=75 | | 2x^2+13x=24 | | -496=-8(-10x-8) | | -165=5(5x-3) | | 5x+1=7+3x | | 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 |